Autotransplantation combined with orthodontic treatment: a case involving the maxillary central incisors with root resorption after traumatic injury - Manuel Marques Ferreira; Hugo M. Ferreira; Filomena Botelho; Eunice Carrilho (Korean Academy of Conservative Dentistry, 2015)
Traumatic dental injury can result in avulsion of anterior teeth. In young patients, it is a challenge to the dental professional because after replantation, late complications such as ankylosis require tooth extraction. Although prosthetic and orthodontic treatment, and implant placement have been described as the options for intervention, autogenous tooth transplantation could be an effective procedure in growing patients if there is a suitable donor tooth available. This case presents the treatment of a patient who suffered a traumatic injury at 9 years old with avulsion of tooth 21, which had been replanted, and intrusion of tooth 11. Both teeth ankylosed; thus they were removed and autotransplantation of premolars was carried out. After transplantation, the tooth underwent root canal treatment because of pulpal necrosis. Orthodontic treatment began 3 months after transplantation and during 7 years' follow-up the aesthetics and function were maintained without signs of resorption.